The influence of suspension properties on the grinding behavior of alumina particles in the submicron size range in stirred media mills - Peukert, Wolfgang; Stenger, Frank; Mende, Stefan; Schwedes, Jörg (Powder Technology, 2005)
The paper shows the possibility to produce alumina nanoparticles in a stirred media mill by an appropriate adjustment of the suspension properties and the milling parameters. Besides a high electrostatic suspension stability that can be realised for metal oxides by means of pH value adjustment small grinding beads favour the production of alumina particles with a median particle size of around 10 nm. In addition to size reduction mechanochemical changes and the formation of alumina hydroxide are detected during wet grinding of alumina. This is analysed by means of X-ray diffraction analysis (XRD), thermogravimetry (TG) and dynamic scanning calorimetry (DSC) measurement and a quantitatively good agreement between the three methods could be obtained. Further, it is proved that the hydroxide produced dissolves at pH values lower than 5 thus influencing the grinding process under these conditions.
Keywords: Mechanochemical effects; Nanosized alumina; Stirred media mill; Suspension properties